Gratification in The Perspective of The Positive Law in Indonesia - Fazzan, Fazzan; Ali, Abdul Karim (Ar Raniry : International Journal of Islamic Studies, 2015)
A set of rules about gratification is a novelty within society and is perceived to collide with the cultural of giving in the Islamic society in Indonesia. This study is aimed to explore the meaning of gratification from the positive perspective of law in Indonesia, and the boundaries of gratification, which is interdicted by the laws. This study used the nor- mative method which analyzes the positive law in Indonesia regulating the gratification. The result of this study shows that gratification in the positive law perspective has a wide meaning including each tribute for civil employee or governance. According to Indonesia laws, gratification could be either positive or negative. Gratification which is allowed by the laws is a gift with a pure tension of the giver to the civil employee or governance without expecting to achieve anything. In contrary, grati- fication which is not allowed by the laws is a gift for the civil employee or governance because of the position in that employment and unrelated with the duty or order.